¿Fue el compromiso y consenso de las élites lo que llevó a la consolidación democrática en Costa Rica? Evidencias de la década de 1950 - Bowman, Kirk S. (2000)
Using empirical evidence the author rejects the hypothesis that it was compromise and consensus among Costa Rican Elites which lead to the consolidation of democracy in Costa Rican, and shows that even in the 1950´s politicians were willing to used force in order to bring down their opponents